2022
DOI: 10.1128/mbio.01601-22
|View full text |Cite
|
Sign up to set email alerts
|

Symbiodiniaceae Are the First Site of Heterotrophic Nitrogen Assimilation in Reef-Building Corals

Abstract: Coral reefs rely upon the highly optimized nutritional symbiosis between corals and Symbiodiniaceae dinoflagellates. Heterotrophic feeding on plankton is key to the resistance of corals to environmental stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…N assimilation pathways in scleractinian corals is an active field of research, and the sampling design used here was not intended to address this issue. Coral N supply relies on two main pathways: PN (by feeding) that ultimately derives its N from dissolved N (Houlbrèque and Ferrier‐Pagès 2009) and dissolved N itself (i.e., NH4+, urea, amino acids, NO3), translocated from the symbiont to the host, by transfer of N‐bearing compounds (Martinez et al 2022) or by symbiont pruning (Boschma 1925; Wiedenmann et al 2023). On the reef flat and at the atoll rim, the relative similarity of normalδ15NNO3+NO2, δ 15 N‐PN, and CS‐δ 15 N values do not allow the stable isotopes to clarify N assimilation pathways for Porites .…”
Section: Discussionmentioning
confidence: 99%
“…N assimilation pathways in scleractinian corals is an active field of research, and the sampling design used here was not intended to address this issue. Coral N supply relies on two main pathways: PN (by feeding) that ultimately derives its N from dissolved N (Houlbrèque and Ferrier‐Pagès 2009) and dissolved N itself (i.e., NH4+, urea, amino acids, NO3), translocated from the symbiont to the host, by transfer of N‐bearing compounds (Martinez et al 2022) or by symbiont pruning (Boschma 1925; Wiedenmann et al 2023). On the reef flat and at the atoll rim, the relative similarity of normalδ15NNO3+NO2, δ 15 N‐PN, and CS‐δ 15 N values do not allow the stable isotopes to clarify N assimilation pathways for Porites .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the amino acid nitrogen isotope analysis showed a different nitrogen signature for symbionts based on orientation. Previous studies have shown that under short laboratory conditions, the symbionts are the first site of heterotrophic assimilation 62 . Since the coral host and symbiont are also known to share nutrients in both directions 62 it would be expected that the hosts and symbionts will reach a steady state where they have a similar signature, which was not the case for the shade-adapted corals.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that under short laboratory conditions, the symbionts are the first site of heterotrophic assimilation 62 . Since the coral host and symbiont are also known to share nutrients in both directions 62 it would be expected that the hosts and symbionts will reach a steady state where they have a similar signature, which was not the case for the shade-adapted corals. Hence, the different signatures between the host and symbionts for the shade-adapted corals suggest unequal sharing of resources, where the symbiont is receiving nutrients obtained from ingested prey by the host 63 , but also has an alternative nutrient source that is not being shared.…”
Section: Discussionmentioning
confidence: 99%
“…However, interpretation of bulk tissue isotope values can sometimes be compromised by overlapping values between predators and potential food items and/or by the difficulty of sampling all possible food items. To address this issue, compound‐specific isotope analyses (CSIA) of fatty acids and amino acids have been successfully used in deep and shallow MAFs to investigate their food sources and to reveal variations in the heterotrophic contribution among conspecific organisms (Gori et al ., 2018; Fox et al ., 2019; Martinez et al ., 2022). The basic principle of CSIA is that some fatty acids and/or amino acids (AAs) are routed directly from the diet into the animal tissue, hence they remain unchanged, while others are biochemically transformed during assimilation.…”
Section: Tools To Assess Heterotrophy In Mafsmentioning
confidence: 99%
“…For instance, metals contained in plankton ingested by the coral host are absorbed by algal symbionts for photosynthesis (Ferrier‐Pagès, Sauzéat & Balter, 2018). Similarly, studies applying CSIA‐AA to nitrogen cycling in symbiotic corals have demonstrated that essential amino acids present in plankton prey are utilised by the algal symbionts instead of the host, although algae can synthesise essential amino acids (Martinez et al ., 2022). Therefore, further research is needed before isotope‐based inferences of heterotrophy can be made (e.g.…”
Section: Knowledge Gapsmentioning
confidence: 99%